1657, Va. Acts 434, Act 3 - (:unkn) unknown (My University, 1657)
That the Lord's day be kept holy, and that no journeys be made except in case of emergent necessity on that day, that no goods be laden in boats nor shooting in guns . . . the party delinquent to pay one hundred pounds of tobacco or laid in the stocks . . .
Keywords: DISCHARGE